The structures of three metabolites of the algal hepatotoxin okadaic acid produced by oxidation with human cytochrome P450 - Liu, Li (2012)
Four metabolites of okadaic acid were generated by incubation with human recombinant cytochrome P450 3A4. The structures of two of the four metabolites have been determined by MS/MS experiments and 1D and 2D NMR methods using 94 and 133 μg of each metabolite. The structure of a third metabolite was determined by oxidation to a metabolite of known structure. Like okadaic acid, the metabolites are inhibitors of protein phosphatase PP2A. Although one of the metabolites does have an α,β unsaturated carbonyl with the potential to form adducts with an active site cysteine, all of the metabolites are reversible inhibitors of PP2A.